- This topic has 1 reply, 1 voice, and was last updated 1 year, 1 month ago by .
Viewing 2 posts - 1 through 2 (of 2 total)
Viewing 2 posts - 1 through 2 (of 2 total)
- You must be logged in to reply to this topic.
Tagged: basic maths, maths
a3 + b3 is equal to = ________
a^{3} + b^{3} formula is (a+b)(a^{2} + b^{2} – ab)
Explanation:
We know the formula of (a+b)^{3}
(a+b)^{3} = a^{3} + b^{3} + 3ab(a+b)
=> a^{3} + b^{3} = (a+b)^{3} – 3ab(a + b)
=> a^{3} + b^{3} = (a+b)((a+b)^{2} – 3ab)
=> a^{3} + b^{3} = (a+b)(a^{2} + b^{2} + 2ab – 3ab)
=> a^{3} + b^{3} = (a+b)(a^{2} + b^{2} – ab)